Endoscopic submucosal dissection versus endoscopic mucosal resection for the treatment of rectal lesions involving the dentate line - Kouladouros, Konstantinos; Jakobs, Johanna; Stathopoulos, Petros; Kähler, Georg; Belle, Sebastian; Denzer, Ulrike (Surgical endoscopy and other interventional techniques, 2024)
Background The ideal treatment of epithelial neoplastic rectal lesions involving the dentate line is a controversial issue. Piecemeal endoscopic mucosal resection (EMR) is the most commonly used resection technique, but it is associated with high recurrence rates. Endoscopic submucosal dissection (ESD) has been shown to be safe and effective for the treatment of rectal lesions, but evidence is lacking concerning its application close to the dentate line. The aim of our study is to compare ESD and EMR for the treatment of epithelial rectal lesions involving the dentate line. Methods We identified all cases of endoscopic resections of rectal lesions involving the dentate line performed in two German high-volume centers between 2010 and 2022. Periinterventional and follow-up data were collected and retrospectively analyzed. Results We identified 68 ESDs and 62 EMRs meeting our inclusion criteria. ESD showed a significant advantage in en bloc resection rates (89.7% vs. 9.7%; P = 0.001) and complete resection rates (72.1% vs. 9.7%; P = 0.001). The overall curative resection rate was similar between both groups (ESD: 92.6%, EMR: 83.9%; P = 0.324), whereas in the subgroup of low-risk adenocarcinomas ESD was curative in 100% of the cases vs. 14% in the EMR group (P = 0.002). There was one local recurrence after ESD (1,5%) vs. 16 (25.8%) after EMR (P < 0.0001), and the EMR patients required an average of three further interventions. Conclusion ESD is superior to EMR for the treatment of epithelial rectal lesions involving the dentate line and should be considered the treatment of choice.